The Effect of Return on Equity, Current Ratio, and Earnings Volatility on Capital Structure - Sugiyanto Ikhsan; Sugiyanto (Universitas Pendidikan Ganesha, 2022)
The company's capital structure is an important aspect for the company's growth in the future. Companies that have an optimal capital structure can be the basis for developing the company in a better direction. The phenomenon of the COVID-19 pandemic has had a major impact on various companies in Indonesia, but it is interesting that health companies are gaining momentum to increase company profits. This study aims to analyze the effect of Return on Equity, Current Ratio, and Earnings Volatility on Capital Structure. This study uses a quantitative approach with descriptive and causal methods, research data using the Indo Farma company (INAF). The researcher uses the main data sources to be processed in this analysis. The results of the data test using eviews-10 are categorized into three parts, namely the descriptive test, the classical assumption test, and hypothesis testing. Based on the results of the study, it shows that ROE has a negative effect on the capital structure, meaning that the lower the ROE, the higher the capital structure. CR has a positive effect on the capital structure, meaning that the higher the CR, the higher the capital structure. Earnings volatility has a positive effect on the capital structure, meaning that the higher the earnings volatility, the higher the capital structure. The results of this study show similarities with previous studies, both in developed countries and emerging market countries.